ANALYSIS OF THE BANK'S FINANCIAL HEALTH LEVEL USING THE CAMEL METHOD AT PT. BPR PIJER PODI KEKELENGEN - Mendrofa, Tuberta Rosviani; Br Siringoringo, Magdalena Judika; Dolok Saribu, Ardin (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
In the banking world, the financial health of banks is very important because the main function of banks is to manage or run consumer money. To achieve good financial health requires maximum performance from the bank, where the bank must maximize its performance by developing works and ideas that are in accordance with current needs and demands. The purpose of this study was to determine how the Bank's Financial Health Level Using the CAMEL Method at PT BPR Pijer Podi Kekelengen for the 2021-2023 Period. This study uses a quantitative descriptive approach with a comparative descriptive analysis method. The results of this study indicate that the assessment of the Bank's financial health level at PT BPR Pijer Podi Kekelengen based on the capital aspect is categorized as less healthy, based on the asset quality aspect it is categorized as healthy. Then based on the management aspect is categorized as quite healthy, based on the rentability aspect is categorized as healthy, and based on the liquidity aspect is categorized as unhealthy.